Rapid review of chemistry for the life sciences and engineering : with select applications - Casparian, Armen S. (Boca Raton CRC Press, 2022)
"This book demystifies chemistry for the non-chemist who, nevertheless, may be a practitioner of some area of science or engineering requiring or involving chemistry. It provides quick and easy access to fundamental chemical principles, quantitative relationships, and formulas"--
Keywords: Chemistry